The analysis of biomorphological features of coxofemoral joint of some ciconiiformes - Мельник, О. П.; Друзь, Н. В. (Scientific Progress & Innovations, 2012)
This article presents the analysis of biomorphological features of hip muscles of representatives of ciconiiformes (red heron, black stork, bittern). It was found that the degree of differentiation of hip muscles of these representatives is caused by walking type of bipedal locomotion and by biomorphological static characteristics, which in turn have influence on the degree of every hip muscle development of this species. Also the degree of development of coxofemoral joint muscles and its muscle groups was determined. It was determined that the mass of the extensor muscles of the hip is more than the flexors. This suggests that the ratio of the hip flexors in this species of birds to the extensor depends on keeping the hip in the gravitational field of the Earth in a certain position during static and locomotion.